Psychosocial work and human rights - Ajduković, Dean (Array, 1999)
Over the past years psychosocial assistance programs were developed aiming to alleviate the hindering effects of exposure to massive trauma. The aftereffects of massive organized violence extend far beyond the mere traumatic exposure, both in time and psychosocial implications. Clearly the social and political circumstances need to provide the context that will allow reduction of violence and promote tolerance. This broader context also includes the human rights issue. Only when violence is over, the trauma healing process can begin that can be greatly facilitated by community-oriented psychosocial programs. After organized violence it should be linked to tolerance building, to increasing the conflict resolution capacities and to development of life skills. It is important to help the survivors not only deal with their stress and trauma, but also give them practical tools regarding everyday problems and defusing of intergroup tensions and hostilities. The challenge is to create effective community-based models and interventions that can help facilitate psychosocial reconstruction of the communities, decrease social tensions among groups that were involved in conflict, provide treatment for the most traumatized individuals and work towards stability, peace and reconciliation. The aims of psychosocial assistance programs, such as empowerment of local communities, helping people deals with their losses and grief, heal from trauma and facilitate personal growth, are all closely related to respecting human rights. In turn, growing respect for human rights also creates the stimulating environment in which respect for individual differences becomes a norm that fosters community trauma healing. This all may lead to community social reconstruction, reconciliation, stability and peace. Thus, psychosocial assistance programs need to work hand in hand with advocacy for human rights because they enhance each others effectiveness. and helps increase the local competence.